Fibrin/hyaluronic acid composite hydrogels as appropriate scaffolds for in vivo artificial cartilage implantation - Rampichová, Michala; Filová, Eva; Varga, Ferdinand; Lytvynets, Andriy; Prosecká, Eva; Koláčná, Lucie; Motlík, Jan; Nečas, Alois; Vajner, Luděk; Uhlík, Jiří; Amler, Evžen (ASAIO journal, 2010)
Hydrogels prepared from a mixture of fibrin and high-molecular weight (MW) hyaluronic acid (HA) were found to be suitable scaffolds for chondrocyte seeding and pig knee cartilage regeneration. Collagen in the hydrogels is not necessary for the formation of biomechanically stable tissue. Regenerated cartilage showed very good biomechanical and histological properties only 6 months after implantation. Notably, the quality of the healing process was dependent on the initial chondrocyte concentration of the scaffolds. These experiments were performed according to good laboratory practice (GLP).
Keywords: Animals; Swine, Miniature; tkáňové podpůrné struktury; chondrocyty; Regeneration; Cartilage; biokompatibilní materiály; Prostheses and Implants; Chondrogenesis; Fibrin; tkáňové inženýrství; miniaturní prasata; Hydrogels; prasata; Chondrocytes; kyselina hyaluronová; Hyaluronic Acid; regenerace; biomechanika; Biocompatible Materials; Materials Testing; Male; chondrogeneze; Swine; hydrogely; fibrin; testování materiálů; chrupavka; Tissue Engineering; protézy a implantáty; zvířata; mužské pohlaví; Tissue Scaffolds; Biomechanical Phenomena